Belt accelerator and use thereof, solid insulating material and anhydride-free insulating system

By using ionizable compounds composed of sulfonium-containing cations and hexafluoroantimate anions as band accelerators, combined with anhydride-free impregnation agents, the problem of insufficient reactivity caused by uneven distribution of band accelerators is solved, and the complete curing and stability of the insulating system is achieved, and the performance effect similar to that of anhydride-containing impregnation agents is achieved.

CN114599720BActive Publication Date: 2025-03-28INNOMOTICS GMBH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080074748.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-04
Filing Date
2020-08-11
Publication Date
2025-03-28
Estimated Expiration
2040-08-11

AI Technical Summary

Technical Problem

In the prior art, when manufacturing anhydride-free insulating system, the distribution of the tape promoter in the impregnating agent is uneven, resulting in insufficient reactivity in the low concentration area and the inability to achieve complete curing, resulting in liquid and non-polymerized parts of the insulating system, affecting its stability and durability.

Method used

An ionizable compound composed of sulfonium-containing cations and hexafluoroantimate anions is used as a cationic band accelerator, combined with an anhydride-free impregnation agent, and an insulating system is manufactured through a vacuum pressure impregnation-VPI process.

Benefits of technology

Even in areas with low tape accelerator concentrations, sufficient reactivity and complete curing can be achieved to produce a stable and tolerant number of defects, with the performance equivalent to an insulating system made with an acid anhydride-containing impregnant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114599720B_ABST
    Figure CN114599720B_ABST
Patent Text Reader

Abstract

The present invention relates to tape accelerators and solid insulating materials with the tape accelerators, such as those that can be used to produce anhydride-free insulation systems for electric motors and generators, for example in the form of wound tape insulation. In particular, the present invention relates to anhydride-free insulation systems that can be produced by vacuum pressure impregnation (VPI) process. Insulation systems of this type include solid insulating materials from which the anhydride-free insulation system is produced by impregnation and / or potting with an impregnating agent and subsequent curing. The present invention provides for the first time a solid insulating material with a tape accelerator and optionally a tape binder matched thereto, which solid insulating material can quickly and completely provide a stable insulation system under conditions such as vacuum pressure impregnation, even in areas where the tape accelerator is poor, using anhydride-free impregnating agents.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to tape accelerators and solid insulating materials having the tape accelerators, such as those that can be used to make anhydride-free insulation systems for electric motors and generators, such as in the form of wound tape insulation. In particular, the present invention relates to anhydride-free insulation systems that can be made by vacuum pressure impregnation (VPI) process. Insulation systems of this type include solid insulating materials from which the anhydride-free insulation system is made by impregnation and / or potting with an impregnating agent and subsequent curing.

[0002] Rotating electrical machines comprise electrical windings, such as stator windings, within a laminated core. The windings consist of electrical conductors, which may have been provided with primary insulation, and solid insulating material as main insulation relative to the laminated core. Without further measures, there is no tight connection between the laminated core, the conductors and the main insulation, which leaves gaps and cavities. These areas are filled with air under atmospheric conditions. This is not permitted in applications in the medium and / or high voltage sector, such as in the case of electric motors and generators or large electrical drives, since partial discharges in the cavities and gaps would destroy the insulation within a very short time. The resulting electrical breakdown would mean, for example, that the motor fails.

[0003] Therefore, for the manufacture of the insulation system, the goal is to have a tight connection between the laminated core, the conductors and the main insulation that is as free of bubbles as possible. This is usually achieved by using a solid insulating material that forms the winding and then impregnating it with a so-called impregnation resin, because it saturates and / or impregnates the solid insulating material.

[0004] In this context, this liquid resin component is referred to as an "impregnant" because, in addition to the actual resin component, i.e. the impregnating resin, it may also contain curing agents, catalysts, diluents, additives, fillers, etc. By potting, in particular also saturating and impregnating the solid insulating material in the laminated core with this impregnant, defects can be minimized.

[0005] Suitable solid insulating materials are, in particular, porous insulating materials, for example mica tapes, insulating papers and / or nonwoven materials (nonwovens), and any combinations thereof.

[0006] For the insulation of rotating electrical machines in the medium and / or high voltage area, windings made of solid insulating material have hitherto been customary in the art, which are impregnated in an impregnating agent by a vacuum pressure impregnation method—VPI—with a mixture of liquid epoxy resin and liquid cyclic anhydride.

[0007] The solid insulating material is formed of a barrier material bonded with a tape adhesive in addition to an optionally present basic skeleton, such as a fabric made of reinforcing fibers. Dissolved and / or finely dispersed therein are so-called "tape accelerators" which first initiate gelation, i.e. the formation of a precured synthetic resin, and then promote complete curing if polymerization of the liquid impregnating agent does not proceed.

[0008] The tape adhesive is used here, for example, for the connection (bonding) of mica paper and carrier materials such as foil and / or glass fabric, while the tape accelerator in proportion leads to the gelation of the thin liquid impregnation resin to form a precured synthetic resin. For this purpose, the liquid impregnating agent, which penetrates into the winding made of solid insulating material, leaches the tape accelerator out of the solid insulating material and thus causes the tape accelerator to migrate and distribute in the impregnating agent. After gelation, the impregnated winding is thermally cured during the production of the finished anhydride-free insulation system.

[0009] However, since the tape accelerator is present in the solid insulating material as a reservoir, a completely uniform distribution of the tape accelerator in the impregnating agent does not occur during the impregnation process. Instead, there are areas of high and low tape accelerator concentrations.

[0010] The anhydrides, in particular cyclic anhydrides, which have hitherto been present in the impregnating agents act firstly as curing agents for the epoxy groups and at the same time reduce the viscosity of the impregnating agent as a whole, which promotes rapid and complete impregnation of the solid insulating material.

[0011] As an industry standard for electric machines, a mixture of distilled bisphenol A diglycidyl ether as impregnating resin and methyl hexahydrophthalic anhydride as anhydride-containing curing agent has been established as an impregnating agent, which together form a very fluid formulation which, without an accelerator, has the required long-term storage stability at room temperature and even at the impregnation temperature. This long-term storage stability is manifested, for example, in a doubling of the dynamic initial viscosity after only a few weeks, whereas in the presence of catalytically active compounds, such as those deposited in the solid insulating material with an accelerator, the mixture reacts rapidly in the impregnating agent to form a high polymer.

[0012] Typically, according to the prior art, the preferred belt accelerator is a compound known as zinc naphthenate which is obtained from mineral oil. However, other synthetic belt accelerators are also known to the person skilled in the art, for example those from EP 0 424 376 B1.

[0013] However, cyclic anhydrides in impregnants are sensitizing compounds, especially in the respiratory tract. This generally calls their unrestricted availability in the future into question. In particular, methylhexahydrophthalic anhydride (MHHPA) has been listed as a candidate substance for substances of particular high concern under REACh legislation since December 2012 due to its respiratory sensitizing properties.

[0014] The development of completely anhydride-free insulation systems for rotating generators and machines in the high-voltage area is therefore of great economic interest.

[0015] However, the use of anhydride-free epoxy resin-based impregnants for the impregnation of rotating electrical machines in the medium- and high-voltage sectors requires a redevelopment of the entire insulation system.

[0016] Specifically, the composition of the solid insulating material, ie, for example, mica tape, and the matching of tape adhesive and tape accelerator must be redesigned to use anhydride-free impregnants.

[0017] Solid insulating materials that react with an anhydride-free impregnation resin based on epoxy resin to form an insulation system are known from EP 3227893, EP 3298611 and WO 2017153113. Tape adhesives for solid insulating materials for impregnation with anhydride-free impregnating agents are also known from EP 3245063.

[0018] However, a disadvantage of the systems known to date is that the reactivity of the tape accelerator / tape binder / impregnating agent mixture is too low and therefore incomplete curing is exhibited in winding regions having a low concentration of tape accelerator.

[0019] In particular, these tape accelerators no longer have sufficient efficacy from a concentration of about 1% by weight or less, so that even after complete impregnation of the solid insulating material with the impregnating agent and gelation and subsequent curing, liquid and non-polymerized portions of the impregnating resin are still present in such amounts that a durable insulation system having only a few defects, such as bubbles, is formed.

[0020] Table 1 shows by way of example the reaction enthalpies of anionic belt promoters known hitherto which react with anhydride-free impregnants, but react too weakly in catalytic amounts of 1% by weight or less, such as are always present in insulating local areas during encapsulation in areas with lower belt promoter concentrations.

[0021]

[0022] -378Jg -1 The reaction enthalpy of -8.3 Jg is sufficient for a stable insulating system, but -1 The reaction enthalpy is not.

[0023] The proportion of impregnating agent which has not yet polymerized can be measured by DSC—differential scanning calorimetry—as incomplete curing via the exotherm of the reaction.

[0024] Figure 1 and 2 Table 1 shows the DSC measurement results.

[0025] Tape promoters with better activity are known, in particular tape promoters with cationically active properties, so-called cationic tape promoters, for example based on quaternary ammonium compounds, but these have the disadvantage that they cannot withstand without damage the temperature increases relative to room temperature that occur during the winding and / or production of solid insulation materials with incorporated tape promoters.

[0026] The object of the present invention is therefore to provide a tape accelerator for incorporation into a solid insulating material with a tape binder, which is suitable for forming an insulation system with an anhydride-free impregnating agent. It is particularly important here that the tape accelerator deposited in the solid insulating material during the impregnation process exhibits sufficient tape accelerator efficacy in winding regions with low tape accelerator concentrations.

[0027] Said object is achieved by the subject matter of the invention as disclosed in the description, the drawings and the claims.

[0028] The present invention therefore provides a cationic tape promoter for use in a method for producing an insulation system by impregnation and / or potting with an anhydride-free impregnating agent, the tape promoter comprising an ionizable compound of one or more sulfonium-containing cations and one or more hexafluoroantimonate anions.

[0029] More specifically, the subject of the present invention is a cationic tape promoter for use in a method for producing an insulation system by potting with an anhydride-free impregnating agent, wherein the tape promoter is a compound covered by one of the structural formulae I, II or III:

[0030]

[0031] Figure 3 The structural formula “Structure I” of a cationic belt accelerator according to a preferred embodiment of the present invention is shown.

[0032] Furthermore, the invention provides for the use of the tape accelerator for producing anhydride-free insulation systems by impregnating solid insulating materials with an impregnating agent, wherein the impregnating agent comprises an aromatic and / or cycloaliphatic impregnating resin which contains epoxy groups and is anhydride-free.

[0033] The subject of the present invention is therefore a solid insulating material as an independently tradable intermediate product, which comprises a barrier material, a tape adhesive and a tape promoter, wherein the tape promoter is a cationic tape promoter and comprises an ionizable compound consisting of a sulfonium-containing cation and a hexafluoroantimonate anion, for example 4-acetoxyphenyl-dimethylsulfonium hexafluoroantimonate (CAS No. 135691-31-5) structure I.

[0034] Structure I

[0035]

[0036] Finally, the subject of the invention is an insulation system which can be produced by potting a solid insulating material with a tape promoter with an anhydride-free impregnating agent, wherein the tape promoter comprises an ionizable compound composed of a sulfonium-containing cation and a hexafluoroantimonate anion, in particular a compound according to formula I.

[0037] The compound according to structure I is in particular a compound commercially available under the name 4-acetoxyphenyl-dimethylsulfonium hexafluoroantimonate.

[0038] The general finding of the present invention is that such a solid insulating material, i.e. a solid insulating material comprising an ionizable compound consisting of a sulfonium-containing cation and a hexafluoroantimonate anion as a cationic tape promoter, in particular a solid insulating material comprising at least a majority of the compound of the formula I as a cationic tape promoter, reacts with an anhydride-free impregnation resin, in particular an epoxy-based impregnation resin, even in the region of low tape promoter concentration, i.e. a tape promoter concentration of 1% by weight or less, to such an extent that the anhydride-free impregnation resin based on epoxy resin gels and / or cures sufficiently during the potting process to produce an insulation system, so that an insulation system that is sufficiently stable and has a tolerable number of defects can be produced in a proven VPI production process and a corresponding VPI system. In terms of defects, the insulation system that can be produced with the tape promoter according to the present invention is comparable to the insulation system that can be produced with the conventional anhydride-containing impregnation agent according to the prior art.

[0039] “Cationic impregnation promoter” is understood to mean an impregnation promoter which is ionizable and whose cations initiate a cationic polymerization, in particular a cationic homopolymerization, of the pregelled impregnation resin in the liquid impregnation agent.

[0040] An "ionizable" compound is a heteropolar compound whose chemical reactivity is determined by the presence of cations and anions in the compound. Traditional "ionizable" compounds are salts. However, complex structures with both cationic and anionic characteristics are also referred to herein as "ionizable" compounds.

[0041] The "sulfonium-containing cation" is an anion which, in addition to an anion and a cation, comprises in the molecule a cation having a monovalent positive charge of structure II or III or of the general formula [SR3] + Unit of description.

[0042] Cation Structure Ⅱ

[0043]

[0044] Diarylalkylsulfonium

[0045] Cationic structure III

[0046]

[0047] Dialkylarylsulfonium

[0048] "Alkylarylsulfonium or dialkylarylsulfonium" refers here to a sulfonium-containing cation in which one or two or three "R" groups on the sulfur atom in the sulfonium cation are alkyl groups. An alkyl group is a part of a molecule that consists of carbon atoms and hydrogen atoms bonded to one another. In the context of the present invention, preferred alkyl groups are those having 1 to 12 carbon atoms, which may be branched or straight-chain. The alkyl group is here monovalently bonded to the central sulfur atom.

[0049] According to the invention, in the dialkylarylsulfonium cation, one or two alkyl groups may be present, which in turn may be identical or different.

[0050] "Arylalkylsulfonium or diarylalkylsulfonium" refers herein to a sulfonium-containing cation wherein one, two, or three "R" groups on the sulfur atom in the sulfonium cation are aryl groups. Aryl groups are moieties that are monovalently attached to a carbon backbone or to a sulfur atom and have at least one aromatic core that may be partially or fully substituted or unsubstituted.

[0051] According to the invention, in the arylalkylsulfonium cation, one or two aryl groups may be present, which in turn may be identical or different.

[0052] The third group may be any group, ie, may also be a fully or partially substituted or unsubstituted alkyl or aryl group.

[0053] Aryl is an organic chemical group with an aromatic skeleton. It is a term for a monovalent atomic group derived from aromatic hydrocarbons by removing a hydrogen atom bonded to a ring. Most aryl groups are derived from benzene, the simplest aryl group being phenyl.

[0054] According to a preferred embodiment, at least one aromatic group is present in the sulfonium cation.

[0055] Here, at least one mononuclear aromatic group is preferably present, ie, for example, an aromatic group having an aromatic structure derived from benzene, such as a phenyl group or a benzyl group.

[0056] More particularly, it is also preferred that at least one substituent is present on the mononuclear aromatic group of the aromatic group of the sulfonium-containing cation, ie a hydrogen on the aromatic core is replaced, for example, by a functional group or an alkyl group.

[0057] The functional groups here may or may not contain heteroatoms such as oxygen, nitrogen, sulfur, phosphorus.

[0058] Particularly preferred are aryl groups in which hydrogens on the aromatic core are replaced by acetoxy groups.

[0059] Furthermore, it is particularly preferred that the band promoter present is a sulfonium-containing cation in combination with a hexafluoroantimonate anion.

[0060] According to one embodiment, essentially one compound is present as a cationic belt promoter.

[0061] In another embodiment, the belt promoter is present as a mixture of at least two cationic belt promoters, which in each case have different sulfonium cations. The anions can be identical or different. More specifically, hexafluoroantimonate is provided as anion.

[0062] Here, a mixing ratio of 1000 parts of the first belt accelerator to 1 part of the second belt accelerator is specified until the first and second belt accelerators are in equal proportions. Preferably, 100 parts of the first belt accelerator are mixed with 1 part of the second belt accelerator. Particularly preferably, 10 parts of the first belt accelerator are mixed with 1 part of the second belt accelerator.

[0063] The belt accelerator, whether present as a single compound or as a mixture, preferably has a melting point in the range of 145°C to 165°C, particularly preferably in the range of 155°C to 160°C.

[0064] "Solid insulating material" more particularly refers to a composite material consisting of a carrier, a barrier material, a tape binder and a tape accelerator. Depending on the size and shape of the barrier material, the carrier is present or absent. The carrier is therefore optional.

[0065] The barrier materials used are electrically insulating materials, in particular materials which can be bonded in particulate form to sheet-like structures such as adhesive tapes, paper, etc. Mica is particularly preferred in this respect, since it also combines a particularly high puncture resistance with a high thermal stability. However, all barrier materials which are suitable for incorporating the tape accelerator according to the invention and for producing an insulation system after potting, impregnation and curing can be used here.

[0066] The barrier material is preferably at least partially in sheet form.

[0067] In an advantageous embodiment, a carrier in the form of a braid, such as a glass fiber braid, a nonwoven material such as a nonwoven, in particular a polyester nonwoven, paper and / or a foil is present in the solid insulating material. The foil-form carrier may also be perforated.

[0068] Preferably, the particulate barrier material is present at, in and / or on such a carrier in the solid insulating material.

[0069] According to one embodiment, a tape adhesive in the form of a glycidyl ether epoxy resin is present in the solid insulating material. In this case, a glycidyl ether epoxy resin having n=0 to n=50, preferably n=1 to n=30, more preferably n=2 to n=18 repeating units is particularly preferably present. The tape adhesive can also alternatively comprise epoxy novolac and / or epoxy-phenol novolac, in particular in the form of those having n=0.1 to n=8 repeating units.

[0070] According to a preferred embodiment of the invention, the solid insulating material comprises a thermoplastic polyvinyl acetal and / or polyester, for example a tape adhesive in the form of a liquid polyester.

[0071] According to an advantageous embodiment, the polyester comprises hydroxyl and / or carboxyl groups as functional units.

[0072] Possible polyvinyl acetals are, for example, butyraldehyde and / or acetaldehyde.

[0073] In principle, tape adhesives containing epoxy groups (epoxy resins) do not exhibit the same good properties as tape adhesives without epoxy groups together with the tape promoter according to the invention. The tape adhesive is present, for example, in the form of a blend, so that a certain proportion of compounds containing epoxy groups is present together with the thermoplastic polyvinyl acetal and / or polyester, wherein preferably the properties of the thermoplastic polyvinyl acetal and / or polyester predominate in the blend forming the tape adhesive.

[0074] The tape adhesive connects at least one carrier and the barrier material in the solid insulating material of the insulation system. Its amount in the solid insulating material is in the range of 1 to 30% by weight, preferably 2 to 15% by weight, more preferably 5 to 10% by weight.

[0075] The tape promoter is introduced into the solid insulating material in tape form and is therefore also referred to as a "tape promoter". This can be done, for example, by surface coating. to achieve.

[0076] For example, the belt accelerator is applied at 0.1 to 5 g / m 2 The coating weight is preferably introduced into the solid insulating material at 0.25 to 2 g / m 2 The coating weight is preferably 0.5 to 1.5 g / m 2 The coating weight is introduced.

[0077] As mentioned above, the impregnating agent mainly includes the impregnating resin, but may also include other components - for example, for changing the processing properties and / or the properties of the molding material - such as curing agents, catalysts, diluents, additives, fillers, etc.

[0078] Suitable impregnating resins in the impregnating agent include cationic polymerizable monomers and / or oligomers. More specifically, suitable impregnating resins include one or more anhydride-free compounds with oxirane and / or epoxy groups. Such / these compounds may be present in whole or in part in aromatic, aliphatic and / or alicyclic forms.

[0079] The following compounds may be mentioned by way of example as suitable impregnating resins, either alone or in the form of mixtures, polymer blends and copolymers:

[0080] - epoxy resins, in particular bisphenol A and / or bisphenol F epoxy resins,

[0081] -phenolic varnish

[0082] - Aliphatic epoxy resin

[0083] - Cycloaliphatic epoxy resin

[0084] - glycidyl ether and / or glycidyl ester compounds of the above resins and

[0085] - Any mixture, blend or copolymer of the above resins.

[0086] In particular blends of cycloaliphatic epoxy resins with aromatic glycidyl ether epoxy resins are suitable impregnating resins in the context of the present invention.

[0087] According to an advantageous embodiment, a mixture of at least one 3,4-epoxycyclohexylmethyl-3′,4′-epoxycyclohexanecarboxylate and an aromatic epoxy resin, for example bisphenol A and / or F diglycidyl ether, is present as the impregnating resin.

[0088] An example of an impregnation resin formulation is a mixture of aliphatic and / or aromatic epoxy resins and at least one cycloaliphatic epoxy resin. The mixing ratio of aliphatic and / or aromatic epoxy resin to cycloaliphatic epoxy resin may be in the range of 80:20 to 5:95, in each case in parts by mass. Preferred mixing ratios are in the range of 50:50 to 10:90 and preferably in the range of 30:70 to 15:85.

[0089] The advantages of the belt promoter according to the invention in combination with an anhydride-free impregnating agent are explained below by means of the drawing, which shows measurements of exemplary belt promoters according to the invention and a comparison with prior art compounds also in connection with anhydride-free impregnating agents.

[0090] The extent of reaction of the tape promoter having structural formula I in the low tape promoter concentration region during potting can also be detected by DSC measurement as shown below.

[0091] Regarding thermal stability of the belt accelerator according to structure I.

[0092] The belt promoters of structure I are cationically active belt promoters.

[0093] Cationic-active tape accelerators are known, for example based on quaternary ammonium compounds, but they have the disadvantage of low thermal stability and decompose significantly even at temperatures well below 100° C., i.e. at processing temperatures of 50° C. to 70° C. This is generally disadvantageous at least for use in the production of insulation systems, since temperatures of about 70° C. can occur during the production of solid insulating materials and also before pressure impregnation during heating of the conductor and before contact with the impregnating agent.

[0094] In contrast, the tape accelerator according to structure I has the advantage that it does not show any significant changes even after a heat treatment at 70° C. for 168 hours. This can also be detected again by DSC measurement. The tape accelerator of structure I is a white crystalline solid at room temperature, the melting point of which can be determined by DSC. If the tape accelerator of structure I is altered and / or damaged by the heat treatment, this will lead to a decrease in the melting point.

[0095] Figure 4 and Figure 5 The results of the corresponding tests are shown.

[0096] Figure 4 A sample with an accelerator according to structure I having a melting point of 160° C. at room temperature known from the literature is shown.

[0097] Figure 5 The same sample is shown after heat treatment for 168 hours at 70° C. The melting point is unchanged.

[0098] Figure 6 The same sample is shown again, Figure 5 After the measurements which can be seen in , the sample was heat treated for a further 24 hours at 80° C. The melting point remained unchanged.

[0099] like Figures 4 to 6 As shown, the tape accelerator according to configuration I can constantly withstand the temperature loads (thermal stresses) occurring during the production of the wound tape insulation and during the preparation for impregnation with the impregnating agent.

[0100] Firstly, the compound can withstand thermal stress unchanged; secondly, the ionizable compound consisting of a sulfonium-containing cation and a hexafluoroantimonate anion, exemplified here by a compound according to structure I, also retains its reactivity towards impregnation resins such as the cycloaliphatic Celloxide 2021P.

[0101] Figure 7 and 8Concentrations below 1 wt % of tape accelerator in a typical impregnating resin (here a cycloaliphatic epoxy resin) are shown. Figure 7 Here the reactivity of the fresh accelerator is shown, and Figure 8 Shows the comparison results as Figure 6 The reactivity after heat treatment of , ie the reactivity of the same belt accelerator after storage for 168 hours at 70° C. and for 24 hours at 80° C. As before with regard to the melting points of the compounds used, the reactivity remains unchanged.

[0102] For comparison, the same test was performed using quaternary ammonium hexafluoroantimonate as the belt accelerator.

[0103] Fresh N-(p-methoxybenzyl)-N,N-dimethylaniline hexafluoroantimonate is also a white crystalline solid. Figures 3 to 8 Like the hexafluoroantimonate sulfonate tested in .

[0104] Fig. 9 A DSC measurement for determining the melting point of fresh N-(p-methoxybenzyl)-N,N-dimethylaniline hexafluoroantimonate is shown. The peak at 116°C indicating the melting point is clearly discernible.

[0105] Fig.10 The same sample is shown after heat treatment at 70°C for 48 hours. The spectrum has changed quite significantly, i.e. the material is no longer in its original state. The peak at 109°C indicates a depression in the melting point due to contamination. Fig.11 The same measurement results are shown for the same sample after a heat treatment for 168 hours at 70° C. The melting point is clearly no longer discernible.

[0106] In order to Figure 7 and 8 For comparison, Figure 7 and 8 The reactivity of the prior art comparative sample N-(p-methoxybenzyl)-N,N-dimethylanilinium hexafluoroantimonate relative to the cycloaliphatic epoxy resin Celloxide 2021P was measured as in the test shown.

[0107] The results are again very clear, because Fig.12 The system with fresh N-(p-methoxybenzyl)-N,N-dimethylaniline hexafluoroantimonate showed adequate reactivity, but the comparison with N-(p-methoxybenzyl)-N,N-dimethylaniline hexafluoroantimonate which had been stored at 70° C. for 48 hours was actually quite unfavorable in terms of reactivity, and—as Fig.13 As shown in the figure, the curing reaction of the prior art belt accelerator N-(p-methoxybenzyl)-N,N-dimethylaniline hexafluoroantimonate is greatly reduced after being stored at 70°C for 168 hours.

[0108] In the following, it is impressively shown on the basis of further tests which properties and / or advantages cationic belt accelerators based on sulfonium cations, in particular dialkylarylsulfonium cations, have compared to customary impregnation resin mixtures formed from aromatic diglycidyl ether epoxy resins, such as EP162, and cycloaliphatic epoxy resins, such as C2021P.

[0109] Of the two resin components, preference is given to using those which in the mixture give a blend with the lowest possible viscosity, since the solid insulating material can be impregnated particularly effectively with them.

[0110] Table 2 shows the viscosity of commercially available epoxy resin mixtures at temperatures between 50°C and 70°C:

[0111] Table 2

[0112]

[0113] Fig.14 A graphical representation of Table 2 is shown. The decrease in viscosity with increasing temperature is clearly identifiable.

[0114] Various concentrations of tape promoter were added to the mixtures of these impregnating resins. A cationic tape promoter according to a preferred embodiment of the present invention is herein designated "SI-150", under which trade name the compound "4-acetoxyphenyl-dimethylsulfonium hexafluoroantimonate" is available.

[0115] By varying the concentration of the tape accelerator, the impregnation resin composition, and the impregnation temperature, the reactivity and / or gelation time and sensitivity to low tape accelerator concentrations can be controlled.

[0116] Tables 3 to 5 show the results of adjusting the gelation time by means of the belt accelerator concentration and / or the impregnation resin composition and / or the temperature.

[0117] Tables 3 to 5

[0118]

[0119]

[0120]

[0121] Fig.15 The gelation time of the mixture of EP162 and C2021P at 70° C. is shown as a function of the SI-150 concentration. The gelation time increases with increasing tape accelerator content, however, gelation is evident even at a very low tape accelerator concentration of 0.1%, so that even such a low concentration of tape accelerator according to the embodiments of the present invention is sufficient to achieve a stable insulation system.

[0122] Fig.16 In comparison, the gelation times are shown at the same concentration of accelerator, but at different temperatures and different impregnation resin mixing ratios. It is once again clear that at a low concentration of 1% SI-150 in the impregnation resin mixture and various concentrations of cycloaliphatic epoxy resin, good gelation times can be achieved in each case at 60° C. and 70° C.

[0123] at last, Fig.17 Shown is the variation of gel time with temperature for mixtures formed from a mixture of 20% EP162 and 80% C2021 with various concentrations of belt accelerator.

[0124] The above tests were all conducted with the belt accelerator as a compound. However, it was found, completely unexpectedly, that mixtures of belt accelerator components can also significantly shorten the gelation time.

[0125] By adding a further cationic sulfonium hexafluoroantimonate compound, benzyl (4-hydroxyphenyl) methylsulfonium hexafluoroantimonate, hereinafter abbreviated as SI-100, to the belt promoter SI-150, the following gelation times summarized in Table 6 were obtained:

[0126] Table 6:

[0127]

[0128] The reactivity and / or sensitivity of the impregnating resin mixture with the tape accelerator mixture can be adjusted via the composition of the impregnating resin. Thus, it was found, completely unexpectedly, that with increasing proportions of cycloaliphatic epoxy resin in the impregnating resin composition, the reactivity of the tape accelerator SI-150 leads to full curability even at tape accelerator concentrations as low as 0.001%.

[0129] This is summarized in Table 7.

[0130] Table 7:

[0131]

[0132] Figures 18 to 21 The curing reaction of various blends in the impregnating resin at low concentrations of tape accelerator such as 1%, 0.1%, 0.01% and finally 0.001% is shown. In the top graph, it can be clearly seen that with the increase of the cycloaliphatic epoxy resin C2021P content, full curing still occurs significantly at a tape accelerator content of 0.001.

[0133] In order to achieve maximum through-cure in the complete mica tape insulation, mixtures having a cycloaliphatic epoxy resin proportion of 70% or more, such as C2021P, are particularly suitable.

[0134] Finally, the performance of the tape accelerator was also examined in conjunction with the tape adhesive.

[0135] In solid insulating materials, such as mica tapes, the tape binder, for example, bonds particles of mica flakes to one another to yield a tape that desirably exhibits a storage stability of at least 3 months, and even better 6 months or more.

[0136] Storage stability is understood here to mean, firstly, that the processing properties thereof are constant. This can be verified, for example, in the case of a belt, by a change in its flexural rigidity.

[0137] The changes in bending stiffness were measured and the results are shown in Tables 8 and 9 and Fig. 22 and 23 as shown in .

[0138] Conventionally used mica tape adhesives are, for example, aromatic glycidyl ether epoxy resins, such as bisphenol A diglycidyl ether or epoxidized phenolic novolacs. These tape adhesives have limited applicability when sulfonium cations with hexafluoroantimonate are used as tape promoters. This can be understood from the storage stability of the correspondingly formed solid insulating material. The storage stability can be identified by measuring the flexural rigidity.

[0139] For example, a conventional solid insulation material which has been treated with a tape accelerator according to the invention, such as SI-150, at a coating weight of 1 g per meter, has an increase in flexural stiffness of more than 50% at 40° C. even after 4 weeks. In contrast, a comparative sample of the same solid insulation material which has not been treated by topcoating with SI-150 shows no increase in flexural stiffness.

[0140] The flexural stiffness is a measure of the processability of a solid insulating material and is desirable to be as close to 0 as possible - for example for the manufacture of windings. In general, a flexural stiffness of more than 70 to 75 N / m is considered here as a critical value for processing.

[0141] Table 8 shows a comparison of two Poroband 4037 mica tapes from Isovolta, one subsequently coated with SI-150 and one not.

[0142] Table 8

[0143]

[0144]

[0145] In tests, it has been found that, by contrast, tape adhesives without epoxy groups, such as thermoplastic polyvinyl acetals, in particular in the case of acetalization with butyraldehyde and / or acetaldehyde, and / or liquid polyesters with hydroxyl and / or carboxyl groups, do not show a significant increase in flexural stiffness when subjected to the same post-treatment with SI-150.

[0146] For example, by Kuraray A mixture of BA55HH polyvinyl acetal and Rokrapol 7075 carboxyl-functional polyester polyol from Robert Kraemer allows the formulation of tape adhesives that have good properties comparable to conventional epoxy-containing tape adhesives, but exhibit significantly better storage stability in combination with SI-150.

[0147] Mica tape sample composed of the following

[0148] -12.25g / m -2 Rokrapol 7075

[0149] -2.00g / m -2 Mowital BA55HH

[0150] -1.00g / m -2 SAN-AID Sl-150

[0151] After 4 weeks of storage at 40°C, the bending stiffness showed an increase of only 14%. The absolute value of 70-75 N / m was not exceeded. -2 .

[0152] Table 9 shows the corresponding measurement results:

[0153] Table 9:

[0154]

[0155] Changes in accelerator activity and / or reactivity

[0156] As a further measure of the storage stability of mica tapes containing tape accelerators, the constancy of the activity and / or reactivity of the tape accelerator is used.

[0157] This can be detected by DSC. For this purpose, the 19-25 mm 2 The reaction of the mica tape sample with 8-9 mg of impregnating resin was exothermic.

[0158] Mica tape sample composed of the following

[0159] -12.25g / m -2 Rokrapol 7075

[0160] -2.00g / m -2 Mowital BA55HH

[0161] -1.00g / m -2 SAN-AID Sl-150

[0162] After storage for 4 weeks at 40° C., no significant changes in the reaction exotherm and peak maximum were shown compared to a mixture of 20% EP162 and 80% C2021P as impregnating resin.

[0163] Fig. 22 The results show that the mixture formed by 20% EP162 and 80% C2021P has a relative -2 Curing reaction of mica tape with 100% SI-150 tape accelerator coating, without thermal post-treatment of the mica tape samples.

[0164] Fig.23 The results show that the mixture formed by 20% EP162 and 80% C2021P has a relative -2 Curing reaction of mica tapes coated with SI-150 tape accelerator, where the mica tape samples were heat stored at 40°C for 4 weeks.

[0165] Features and advantages of tape accelerators in combination with mica tapes and anhydride-free impregnation resins in terms of the accelerator action range:

[0166] The extent of the effect of the tape accelerator of a mica tape can be shown in a simple experiment. For this purpose, a mica tape sample with the dimensions of 400x25 mm is wound onto a 4 mm thick mandrel. The roll obtained in this way is pulled off the mandrel and placed with tweezers in front of the curved base of a test tube, which in the experiment was 16 x 160 mm and thick-walled. This is then filled with 4.4 g of preheated impregnation resin—for example 70° C. The impregnation resin is then slowly introduced into the roll, so that the curved base and the gaps in the roll are also filled. A resin excess of about 10 mm remains.

[0167] The rolls thus prepared were then subjected to a curing procedure in an air circulation oven and then evaluated for complete curing, especially at the bottom, in the gaps and excesses, as well as on the roll itself.

[0168] Mica tape sample composed of the following

[0169] -12.25g / m -2 Rokrapol 7075

[0170] -2.00g / m -2 Mowital BA55HH

[0171] -1.00g / m -2 SAN-AID Sl-150

[0172] A mixture of 20% EP162 and 80% C2021P was used as the impregnation resin in this test, showing complete curing of the roll and all resin areas.

[0173] Finally, dielectric properties are measured to determine the suitability of the insulation system:

[0174] The electrical properties of this type of mica tape in combination with an anhydride-free impregnation resin based on epoxy resin are also given. Thus, a mica tape with the following composition is provided:

[0175] -12.25g / m - 2Rokrapol 7075

[0176] -2.00g / m - 2Mowital BA55HH

[0177] -1.00g / m - 2SAN-AID Sl-150

[0178] In combination with a mixture of 20% EP162 and 80% C2021P as impregnating resin, after 10 hours / 145°C curing, an insulation system with a low electrical loss factor tanδ in the temperature range from room temperature to 155°C is presented, such as Fig.24 as shown in .

[0179] Fig.24 The temperature-dependent change in the loss factor tan δ of an insulation system consisting of a mica tape sample according to an embodiment of the present invention having a tape accelerator coating of 1 g / m, impregnated or soaked with an impregnant comprising a mixture of 20% EP162 and 80% C2021P, and finally cured at 145° C. for 10 hours is shown.

[0180] The present invention provides for the first time a solid insulating material with an accelerator and optionally a matching adhesive, which can quickly and completely provide a stable insulation system with a low number of defects even in areas where the accelerator is poor using anhydride-free impregnants under vacuum pressure impregnation (VPI) conditions.

Claims

1. A solid insulating material comprising a barrier material, a tape binder and a cationic tape promoter, the solid insulating material being used for making an insulation system by impregnation and / or potting with an anhydride-free impregnating agent, wherein during the impregnation and / or potting process, the anhydride-free impregnating agent is capable of penetrating into a winding made of the solid insulating material and leaching the tape promoter from the solid insulating material, the tape promoter being further distributed in the anhydride-free impregnating agent to promote its curing, the concentration of the tape promoter in the anhydride-free impregnating agent having an inhomogeneous distribution and locally being less than 1% by weight, the tape promoter comprising an ionizable compound formed by one or more sulfonium-containing cations and one or more hexafluoroantimonate anions, wherein a substituted aryl group is present in at least one type of the sulfonium-containing cation, wherein the aryl group comprises a benzene ring substituted by an acetoxy group. 2 . The solid insulating material according to claim 1 , wherein at least one arylalkylsulfonium cation is present as the sulfonium-containing cation.

3. The solid insulating material according to claim 1 or 2, wherein at least one dialkylarylsulfonium cation and / or diarylalkylsulfonium cation is present as the sulfonium-containing cation.

4. The solid insulating material according to claim 1, wherein the band accelerator has the following chemical structure: Structure I: The solid insulating material according to claim 1 , wherein the barrier material is in the form of a sheet. The solid insulating material according to claim 1 , further comprising a carrier.

7. The solid insulation material according to claim 6, wherein the carrier comprises a woven fabric, a non-woven fabric, a foil and / or a perforated foil.

8. The solid insulating material according to claim 1, comprising a tape adhesive in the form of a thermoplastic polyvinyl acetal and / or in the form of a liquid polyester which may comprise hydroxyl and / or carboxyl groups.

9. A solid insulating material according to claim 8, comprising a tape adhesive in the form of a polyvinyl acetal based on butyraldehyde and / or acetaldehyde.

10. Insulation system comprising a winding of a solid insulating material according to any of the preceding claims 1 to 9 impregnated with an anhydride-free impregnating agent.

11. An electrical machine comprising an insulation system according to claim 10.

Citation Information

Patent Citations

  • Insulating tape for making an insulating sheath impregnated with a heat-curing epoxide resin / acid anhydride mixture for electrical conductors

    EP0424376B1

  • Insulating tape for a coil and wrapping tape insulation system for electric machines

    EP3227893A1

  • Tape adhesive for an insulating tape in an insulation system and insulation system

    EP3245063A1

  • Solid insulation material, use thereof and the thus produced insulation system

    EP3298611A1

  • Solid insulation material, use thereof, and insulation system made therewith

    WO2017153113A1